Amebicidal Activity of Escherichia coli Nissle 1917 Against Entamoeba histolytica - Vivian Moura-Oliveira; Fabrício M. S. Oliveira; Olga L. M. Moreno; Julia R. Ferreira; Raphael E. Szawka; Ana C. Campideli-Santana; Jullia Teles; Luciano S. A. Capettini; Flaviano S. Martins; Maria A. Gomes (Microorganisms)
Amebiasis is a globally prevalent infection that can lead to fatal outcomes if not adequately treated. Conventional treatment with imidazoles often fails due to side effects and resistance, emphasizing the need for alternative therapies. The probiotic Escherichia coli Nissle 1917 (EcN) has shown potential in combating intestinal pathogens. This study aimed to evaluate the amebicidal activity of EcN in vitro and its effect on the production of reactive oxygen species (ROS). Trophozoites of Entamoeba histolytica (2.5 × 10⁴ cells/mL) were cultured in 96-well plates and exposed to varying concentrations of EcN (102–109 cells/mL). Plates were incubated at 36 °C for 6, 12, and 18 h, after which trophozoite viability was assessed. Intracellular ROS production, including superoxide and hydrogen peroxide, was measured using fluorescent probes. The highest efficacy was observed after 18 h at a CFU concentration of 109 cells/mL. Increased ROS production at all probiotic concentrations suggested a role in EcN’s amebicidal mechanism. Morphological changes in trophozoites, such as rounding, vacuolization, and size reduction, were noted after EcN exposure, indicating growth inhibition. These findings suggest EcN induces structural and morphological changes in E. histolytica, inhibiting its growth in vitro. The findings suggest the potential efficacy of EcN; however, definitive confirmation requires data from human clinical trials.